Análise e dimensionamento de cortinas de estacas moldadas no local - Ferrandin, Eduardo Rafael (2012)
Due to increasing occupancy rate in urban areas is increasingly common use of basements in buildings, and therefore implementation of containment structures is required. Very common, curtain poles molded in place is a simple and economical solution, however, due to sizing errors, many of these structures have presented serious problems both for the building that contains it and especially for neighboring buildings. In this study, we sought to establish a general analytical solution for calculating these structures, using deductions of soil mechanics and settling calculation equations. Subsequently held a case study of a curtain to contain a basement to be executed in the city of Toledo-PR, with digging height equal to 3m. It was found that the definition of geotechnical properties, especially cohesion, are important for a correct dimensioning. A simple variation of the cohesion of zero to 1kN / m², 44.32% change in the value of the characteristic time.